2013
DOI: 10.3109/17453674.2013.765639
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for osteoporosis are common in young and middle-aged patients with femoral neck fractures regardless of trauma mechanism

Abstract: Background and purpose There have been few prospective studies examining young and middle-aged patients with hip fracture. We therefore investigated background data, risk factors, and the trauma mechanism in young and middle-aged patients with femoral neck fracture.Patients and methods 185 patients, 27 young (20–49 years old) and 158 middle-aged (50–69 years old) were prospectively included in a multicenter study lasting 3 years. Background data and risk factors for osteoporosis and fracture were obtained, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 20 publications
(35 reference statements)
6
38
0
Order By: Relevance
“…Al-Ani et al. (2013) found that the majority of these patients had at least one risk factor for fracture and also low mineral density, although they patients were generally reasonably healthy. We therefore hypothesize that the higher mortality observed in patients less than 65 years of age with proximal fractures might be due different factors, such as a risky lifestyle and substance abuse (Levy et al.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Ani et al. (2013) found that the majority of these patients had at least one risk factor for fracture and also low mineral density, although they patients were generally reasonably healthy. We therefore hypothesize that the higher mortality observed in patients less than 65 years of age with proximal fractures might be due different factors, such as a risky lifestyle and substance abuse (Levy et al.…”
Section: Discussionmentioning
confidence: 99%
“… 2011 , Al-Ani et al. 2013 ). However, closed reduction and IF for patients under 60 years of age is usually recommended as many surgeons are reluctant to replace a native hip joint with an arthroplasty (Bhandari et al.…”
mentioning
confidence: 98%
“…Although the overall hip fracture incidence has not changed in the last two decades, in the last 5 years, the incidence has remained stable in women but increased in men [8]. A recent article [9] stated that a small portion of femoral neck fractures in young adults are caused by highenergy trauma, while lifestyle factors and other nontraumarelated risk factors are major contributors. Several authors from different countries have reported high rates of alcohol consumption in younger patients with hip fracture [10], but we have not identified any reports with incidences as high as those in our study.…”
Section: Discussionmentioning
confidence: 99%